Synthesis and Photocatalytic Activity of Pt-Deposited TiO2 Nanotubes (TNT) for Rhodamine B Degradation - Xiaojian Qiu; Zhenning Wan; Mengjie Pu; Xiuru Xu; Yuanyao Ye; Chunhua Hu (Frontiers in Chemistry, 2022)
Dye wastewater has attracted more and more attention because of its high environmental risk. In this study, a novel TiO2 nanotube (TNT) catalyst was prepared and its morphology and structure were characterized. The synthetic catalyst was used to degrade Rhodamine B (RhB) under UV light and evaluated for the application performance. According to the characterization results and degradation properties, the optimum synthetic conditions were selected as 400°C calcination temperature and 10 wt% Pt deposition. As a result, the degradation efficacies were sequenced as TNT-400-Pt > TNT-500-Pt > TNT-400 > TNT-300-Pt. In addition, the effect of pH and initial concentration of RhB were explored, and their values were both increased with the decreased degradation efficacy. While the moderate volume of 11 mm of H2O2 addition owned better performance than that of 0, 6, and 15 mm. Scavengers such as tertbutanol (t-BuOH), disodium ethylenediaminetetraacetate (EDTA-Na2), and nitroblue tetrazolium (NBT) were added during the catalytic process and it proved that superoxide radical anions (O2–•), photogenerated hole (h+) and hydroxyl radical (OH•) were the main active species contributing for RhB removal. For the application, TNT-Pt could deal with almost 100% RhB, Orange G (OG), Methylene blue (MB), and Congo red (CR) within 70 min and still kept more than 50% RhB removal in the fifth recycling use. Therefore, TNT-Pt synthesized in this study is potential to be applied to the dye wastewater treatment.